High-Molecular-Weight Protein (pUL48) of Human Cytomegalovirus Is a Competent Deubiquitinating Protease: Mutant Viruses Altered in Its Active-Site Cysteine or Histidine Are Viable - Wang, Jianlei (American Society for Microbiology, 2006)
We show here that the high-molecular-weight protein (HMWP or pUL48; 253 kDa) of human cytomegalovirus (HCMV) is a functionally competent deubiquitinating protease (DUB). By using a suicide substrate probe specific for ubiquitin-binding cysteine proteases (DUB probe) to screen lysates of HCMV-infected cells, we found just one infected-cell-specific DUB. Characteristics of this protein, including its large size, expression at late times of infection, presence in extracellular virus particles, and reactivity with an antiserum to the HMWP, identified it as the HMWP. This was confirmed by constructing mutant viruses with substitutions in two of the putative active-site residues, Cys24Ile and His162Ala. HMWP with these mutations either failed to bind the DUB probe (C24I) or had significantly reduced reactivity with it (H162A). More compellingly, the deubiquitinating activity detected in wild-type virus particles was completely abolished in both the C24I and H162A mutants, thereby directly linking HMWP with deubiquitinating enzyme activity. Mutations in these active-site residues were not lethal to virus replication but slowed production of infectious virus relative to wild type and mutations of other conserved residues. Initial studies, by electron microscopy, of cells infected with the mutants revealed no obvious differences at late times of replication in the general appearance of the cells or in the distribution, relative numbers, or appearance of virus particles in the cytoplasm or nucleus.